Correlates of employment and postsecondary education enrolment in Afghanistan and Iraq veterans with traumatic brain injuries. (16th April 2018) - Olsen, Donald C; Hays, Chelsea C; Orff, Henry J; Jak, Amy J; Twamley, Elizabeth W
ABSTRACT: Primary Objective: About 20% of Iraq and Afghanistan Veterans have sustained a traumatic brain injury (TBI), which can result in postconcussive symptoms and difficulty transitioning from the military to civilian employment and postsecondary education. To better inform programs help Veterans transition back into civilian life, we evaluated correlates of employment and postsecondary education enrolment among treatment-seeking Veterans with a history of TBI. Research Design: A cross-sectional design, using an archival database of VA medical records, was used to answer these research questions. Methods and Procedures: We examined demographic, TBI-related, postconcussive, psychiatric, and neuropsychological factors in 390 Veterans (86% with mild TBI) to determine what factors were associated with employment or enrolment in postsecondary education. Bivariate correlations and multivariate regression were used. Main Outcomes and Results: age, minority status, and service connected disability ratings were significantly associated with employment and postsecondary education enrolment in a multivariate context, whereas TBI-related factors and neurocognitive, postconcussive, and psychiatric symptom severity were not associated with employment or postsecondary education outcomes. Conclusions: Further research is needed to confirm these findings and to evaluate the contribution of age, minority status, and disability on successful return to work and/or school for Veterans with a history of TBI.